Fe(III)-salen encapsulated Al-MCM-41 as a catalyst in the polymerisation of bisphenol-A - Hamdan, Halimaton; Navijanti, Vivin; Nur, Hadi; Muhid, Mohd Nazlan Mohd (Elsevier, 2005)

(untitled)
Fe(III)-salen complexes encapsulated in the channels of Al-MCM-41 molecular sieves were successfully synthesised in situ by the flexible ligand method. The resulting compound was characterised by XRD, IR spectroscopy, nitrogen adsorption isotherm and 1H NMR techniques. The loading of complexes in Al-MCM-41 depends on the quantity of framework aluminium, suggesting that there is an electrostatic interaction between the positive charges of the encapsulated Fe(III)-salen complexes and the negative charges of the Al-MCM-41 framework. Polymerisation of bisphenol-A catalysed by Fe(III)-salen-Al-MCM-41 gave 67% conversion; significantly higher than the conventional homogeneous Fe(III)-salen catalyst.